Crude cellulase from oil palm empty fruit bunch by Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2 for fermentable sugars production - Ibrahim, Mohamad Faizal; Abdul Razak, Mohamad Nafis; Phang, Lai Yee; Hassan, Mohd Ali; Abd. Aziz, Suraini (Springer, 2013)
Cellulase is an enzyme that converts the polymer structure of polysaccharides into fermentable sugars. The high market demand for this enzyme together with the variety of applications in the industry has brought the research on cellulase into focus. In this study, crude cellulase was produced from oil palm empty fruit bunch (OPEFB) pretreated with 2 % NaOH with autoclave, which was composed of 59.7 % cellulose, 21.6 % hemicellulose, and 12.3 % lignin using Trichoderma asperellum UPM1 and Aspergillus fumigatus UPM2. Approximately 0.8 U/ml of FPase, 24.7 U/ml of CMCase and 5.0 U/ml of β-glucosidase were produced by T. asperellum UPM1 at a temperature of 35°C and at an initial pH of 7.0. A 1.7 U/ml of FPase, 24.2 U/ml of CMCase, and 1.1 U/ml of β-glucosidase were produced by A. fumigatus UPM2 at a temperature of 45°C and at initial pH of 6.0. The crude cellulase was best produced at 1 % of substrate concentration for both T. asperellum UPM1 and A. fumigatus UPM2. The hydrolysis percentage of pretreated OPEFB using 5 % of crude cellulase concentration from T. asperellum UPM1 and A. fumigatus UPM2 were 3.33 % and 19.11 %, with the reducing sugars concentration of 1.47 and 8.63 g/l, respectively.